If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -8 = 40 Reorder the terms: -8 + -2x = 40 Solving -8 + -2x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -2x = 40 + 8 Combine like terms: -8 + 8 = 0 0 + -2x = 40 + 8 -2x = 40 + 8 Combine like terms: 40 + 8 = 48 -2x = 48 Divide each side by '-2'. x = -24 Simplifying x = -24
| 5x+10x-(8x+10)= | | 60-24y= | | 35x^2-6x-9=0 | | 3b^2-19b+30= | | -5x-34=66 | | 62z-(45z+66)= | | 2x^4+5x^3+5x^2+20x-12=0 | | (n-10)-7n=62 | | 1.3x+.4=1.7 | | X^2-400x+20000=0 | | 2x+7(x+3)=9(x-1)+5 | | 8s+15=0 | | 2n^2+13n-24= | | 2z^4-13z^2+36=0 | | 5(n-12)-7n=62 | | 5x-4(x-3)=16 | | 4(4e+1)=12 | | 2x+12-8x=9x-5 | | 5x+15=2x+q | | 3(n-10)-7n=62 | | -9y-39= | | .25+4=18 | | 11m-10m=9m | | 3(n-10)-7n=18 | | 12w-14w=6 | | n-5m=9 | | -2.4x-1=-2.2x+7 | | 5(n-10)-7n=62 | | 9+2=15 | | 17(x-7)=-8-9 | | 3x+4(3x+5)=25 | | 28=2h+18 |